2007
DOI: 10.1159/000101925
|View full text |Cite
|
Sign up to set email alerts
|

Force and Geometry Determine Structure and Function of Glaucoma Filtration Capsules

Abstract: Background/Aims: Glaucoma shunts vent aqueous humor to orbital tissue across a fibrous capsule. The capsule consists of collagen and fibroblasts, and its formation was assumed to be a cicatricial process. Capsule fibrosis remains the leading cause of device failure. We tested the wound healing hypothesis using morphometry and polarization microscopy and found the capsule consists not of scar tissue but rather highly organized extracellular matrix. Methods: Polarization microscopy reveals collagen orientation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“… 15 16 This thickened wall provides increased resistance to being crossed by the aqueous humor may thus result in an IOP increase. 17 18 As the aqueous humor (AH) content of inflammatory cytokines is related to the IOP level, then at least initially, the subconjunctival space of high-IOP patients would be bathed by AH with higher concentrations of inflammatory cytokines. 6 This might be an explanation as to why valved implants are associated with greater thickness of the capsular wall 19 and more probability of bleb dysmorphia and creation of giant reservoirs, 20 21 as nonvalved surgery is usually done resorting to techniques that prevent, at least in an early stage, a free drainage of aqueous humor.…”
Section: Discussionmentioning
confidence: 99%
“… 15 16 This thickened wall provides increased resistance to being crossed by the aqueous humor may thus result in an IOP increase. 17 18 As the aqueous humor (AH) content of inflammatory cytokines is related to the IOP level, then at least initially, the subconjunctival space of high-IOP patients would be bathed by AH with higher concentrations of inflammatory cytokines. 6 This might be an explanation as to why valved implants are associated with greater thickness of the capsular wall 19 and more probability of bleb dysmorphia and creation of giant reservoirs, 20 21 as nonvalved surgery is usually done resorting to techniques that prevent, at least in an early stage, a free drainage of aqueous humor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that fibroblasts react to mechanical stress by increasing the expression of actin stress fibers as well as ECM components. 41 Wilcox and Kadri 14,15 presented evidence that this mechanism is active in tenon fibroblasts around the GDD, showing that collagen fibers and cells align along the direction of tension caused by sharp edges or bulky base plates. The RhoA/Rock signaling pathway appears to play a prominent role in this response to mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the choice of biomaterial is believed to influence the initial inflammatory response to the implant, 12 whereas shape, size, and rigidity of the base plate are thought to influence fibroblast growth and extracellular matrix (ECM) deposition through mechanically induced activation of the cells. [13][14][15] One aspect of implant design that has been largely ignored is the surface texture of the base plate. Since the surface constitutes the major site of interaction with the surrounding tissue, topographic features as well as surface chemistry may well influence wound healing and the fibrotic response.…”
mentioning
confidence: 99%
“…The tube drains AH into the space created by the plate body, located in a subconjunctival space over the sclera (Figure 1a). Over time, a fibrous capsule of tissue, or "bleb," is formed around the AGDD, serving as a reservoir for the extra AH that drains from the eye [23][24][25][26][27][28][29] . In a well-functioning implant with a controlled IOP, the bleb has a thickness of less than 500 μm 24 .…”
Section: Introductionmentioning
confidence: 99%